Apoptosis and Caspase 3 Pathway Role on Anti-Proliferative Effects of Scrophulariaoxy Sepala Methanolic Extract on Caco-2 Cells - Namvaran, Ali; Fazeli, Mehdi; Farajnia, Safar; Hamidian, Gholamreza; Rezazadeh, Hassan (Drug Research, 2017)
Colorectal cancer is one the most important malignancies worldwide and finding new treatment option for this cancer is of high priority. Natural compounds are common source of drugs for treatment of various diseases including cancers. The aim of this study was to investigate the effects of Scrophularia oxysepala extract on Caco-2 cells and explore the possible role of caspase 3 pathway in inducing cell death in this cancer cells in compare with chemotherapy agents of cisplatin and capecitabine. The methanolic extract of Scrophularia oxysepala (SO) was prepared by drench method. The IC50 of extract, cisplatin and capecitabine on Caco-2 cells were determined by MTT assay. The effect of SO extract on caspase 3 expression and inducing apoptosis were determined using TUNEL assay and caspase 3 ELISA methods, respectively. The IC50 of SO extract, cisplatin and capecitabine were 300, 195 and 80 µg/ml, respectively. Analysis for apoptosis revealed that SO methanolic extract increased apoptosis significantly (P<0.001) compared with control group. The effect of high doses of SO extract on apoptosis induction were comparable to cisplatin but significantly were higher than capecitabine. Only high doses of SO methanolic extract showed significant effects (P<0.05) on increasing caspase 3 compared to control group. The methanolic extract of SO showed inhibitory effect on Caco-2 cells and induced apoptosis in a dose-dependent manner comparable to cisplatin and higher than capecitabine 2 commonly used chemotherapeutic agent for various cancers.
Keywords: scrophularia oxysepala; caco-2; apoptosis; caspase 3